‘Who Has the Stick Has the Buffalo’: Processes of Inclusion and Exclusion on a Pasture in the Indian Himalayas - Richard Axelby (South Asia Multidisciplinary Academic Journal)
Based on ethnographic fieldwork conducted over a period of ten years this article details the access arrangements that govern the use of a grazing pasture in Chamba District of Himachal Pradesh, India. Following Ribot and Peluso’s (2003) distinction between ‘property’ and ‘access’ I explore the area between that which people have property rights to, and that which they are able to extract benefit from. In parallel to this Sikor and Lund (2009) identify a second ‘grey zone’ existing between authority and power where decisions about how resources are distributed in society are legitimised. Taking as its subject the multiple ways that these two sets of relationships play out, this article considers the everyday politics through which Gaddi shepherds and Gujjar buffalo herders activate and justify their presence on the pasture. Examining the politics of natural resource use in this way brings to the fore inequalities in access and explains the ways in which they occur.